International business, innovation and ambidexterity: A micro-foundational perspective. Issue 3 (June 2022) - Liu, Yipeng; Collinson, Simon; Cooper, Sir Cary; Baglieri, Daniela
Highlights: Examining the multifaceted aspects of innovation and ambidexterity in international business studies is in greater demand. Investigating the micro-foundations from a multidisciplinary perspective in varying contexts is urgently needed. We highlight the key insights and contributions of the papers included in this special issue. We outline a future research agenda that can help advance on international business and innovation research. Abstract: Research on international business and innovation has accumulated a vast body of knowledge which has assisted in comprehending complex international management issues in diverse international settings. Yet, the existing studies have not paid sufficient attention to the multifaceted aspects of innovation and ambidexterity. We join the conversation with international business and innovation by suggesting that investigating the micro-foundations from a multidisciplinary perspective situated in varying international contexts can advance our collective understandings of the phenomena in important ways. This paper has three general objectives. First, we show that innovation and ambidexterity has been a long-standing issue in international management and business studies and provide an overview of the puzzles that underpin and trigger this special issue. Second, we highlight the key insights and contributions of the papers included in this special issue by reviewing their theoretical underpinnings, methodological approaches and findings. Finally, we outline a future research agenda that can help advance on international business and innovation research.